Peran Psikologi dalam Pendidikan Islam - Kurniyadi, Mahmud Darul; Amin, Ahmad Yasir Al; Rohimah, Siti (Lembaga Yasin AlSys, 2024)
Psychology plays a significant role in Islamic education as a tool to understand and support the holistic development of students. Islamic educational psychology combines spiritual values with psychological aspects to create a learning environment that is in line with the teachings of Islam. This allows educators to better understand the individual characteristics of students, develop teaching skills, provide counseling and guidance in accordance with Islamic values, and manage classrooms effectively. The application of psychological principles in Islamic education enables the formation of quality individuals with noble character. Thus, psychology plays a crucial role in supporting holistic and sustainable Islamic education. Therefore, a deep understanding of the role of psychology in Islamic education is highly relevant and important for advancing an educational system that is oriented towards the development of individuals who are believers, have noble character, and are beneficial to society and the environment.